Connexins in Lung Cancer and Brain Metastasis - Luo, Kai-Jun; Chen, Chang-Xu; Yang, Jia-Peng; Huang, Yun-Chao; Cardenas, Eduardo R.; Jiang, Jean X. (Frontiers in Oncology, 2020)
Connexins (Cxs) are associated with brain metastasis of lung cancer cells. Thus, it is necessary to determine whether gap-junction-forming Cxs are involved in communication between lung cancer cells and host cells, such as the endothelial cells forming the brain-blood-barrier and cells in the central nervous system. Data from multiple studies support Cxs as tumor suppressors during lung cancer occurrence. However, recently, evidence suggests that during cancer metastasis to the brain, cancer cells may establish communication with host cells in a gap-junction-dependent or independent manner. The current review discusses gap junction studies in lung cancer development and brain metastasis, highlighting important unanswered questions and controversies.